2022
DOI: 10.1017/s2040174422000083
|View full text |Cite
|
Sign up to set email alerts
|

Adulthood asthma as a consequence of childhood adversity: a systematic review of epigenetically affected genes

Abstract: There is an accumulating data that shows relation between childhood adversity and vulnerability to chronic diseases as well as epigenetic influences that in turn give rise to these diseases. Asthma is one of the chronic diseases that is influenced from genetic regulation of the inflammatory biomolecules and therefore the hypothesis in this research was childhood adversity might have caused epigenetic differentiation in the asthma-related genes in the population who had childhood trauma. To test this hypothesis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Houtepen identified a locus in the Kit ligand gene (KITLG; cG27512205) which associated with cortisol stress response using genome-wide analysis, and shedding light on the neurobiological pathways behind individual’s vulnerability to stress ( 31 ). Saygideger conducted a meta-analysis and revealed that childhood trauma induces asthma or other chronic inflammatory diseases by influencing genes such as NR3C1 and FKBP5, which mediate immune inflammation ( 43 ). The above studies suggest that FKBP5 methylation, NR3C1 methylation, KITLG methylation, and inflammatory phenotypes have been the focus of epigenetic studies in the field of childhood trauma in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Houtepen identified a locus in the Kit ligand gene (KITLG; cG27512205) which associated with cortisol stress response using genome-wide analysis, and shedding light on the neurobiological pathways behind individual’s vulnerability to stress ( 31 ). Saygideger conducted a meta-analysis and revealed that childhood trauma induces asthma or other chronic inflammatory diseases by influencing genes such as NR3C1 and FKBP5, which mediate immune inflammation ( 43 ). The above studies suggest that FKBP5 methylation, NR3C1 methylation, KITLG methylation, and inflammatory phenotypes have been the focus of epigenetic studies in the field of childhood trauma in recent years.…”
Section: Discussionmentioning
confidence: 99%